Comparative analysis of the labor market integration of international immigrants in the Southeast region of Brazil over 50 years - Elaine Meire Vilela (Geografares, 2023)
The purpose of this article is to examine whether the socioeconomic situation of international immigrants in the labor market differs from that of Brazilians residing in the Southeast region, to understand which groups of immigrants have a worse socioeconomic status than native Brazilians. I use data from the 1970, 1980, 1991, 2000, and 2010 censuses. The results show no pattern in the effect of country of birth on wage differentials over time and across states located in the Southeast region. It is also observed that immigrants from less developed countries, such as Bolivians, tend to be disadvantaged in the labor market, regardless of the state analyzed. However, some cases stand out, such as Germans in Espírito Santo.
Keywords: international immigrants; Brazilian Southeast; labor market